The recruit - Birnbaum, Roger; Apple, Jeff, 1954-; Barber, Gary.; Towne, Roger; Wimmer, Kurt, 1964-; Glazer, Mitch; Donaldson, Roger; Pacino, Al, 1940-; Farrell, Colin, 1976-; Moynahan, Bridget, 1972-; Macht, Gabriel, 1972-; Dryburgh, Stuart; et al. ([United States] : Touchstone Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2003)
Clayton recently completed his studies at MIT. One evening, Clayton is approached by Walter Burke, a recruiter for the CIA, and believes Clayton is just the sort of man the CIA is looking for. Clayton, who has little interest in an ordinary nine-to-five career and accepts the offer. Clayton has to keep in mind Burke's dictum that "nothing is as it seems," especially when Clayton is given a special assignment -- find the mole within the Agency's training program who is actually feeding information to America's enemies.
Special features: deleted scenes with optional commentary; "Spy school: inside the CIA Training program" a never-before-seen look inside the CIA; feature commentary with director Roger Donaldson and Colin Farrell.
Director of photography, Stuart Dryburgh ; editor, David Rosenbloom ; music, Klaus Badelt ; costume designer, Beatrix Aruna Pasztor ; production designer, Andrew McAlpine.
Al Pacino, Colin Farrell, Bridget Moynahan, Gabriel Macht.
MPAA rating: PG-13; for violence, sexuality and language.
Also issued on VHS.
DVD, 5.1 Dolby digital, 5.1 DTS ES, Region 1 encoding.
Keywords: United States. -- Central Intelligence Agency -- Drama; Intelligence officers -- Drama; Employees -- Recruiting -- Drama; Feature films; Suspense films; Video recordings for the hearing impaired